A Study on Thermal Behaviour of Thermoplastic Starch Plasticized by Emim Ac and by Emim Cl - Ismail, S. (Elsevier Ltd, 2017)
Thermoplastic starch (TPS) is a material that's been produced through a gelatinization process at elevated temperature in the presence of plasticizers. However, the hydrophilic properties of structural starch may decrease the thermal behaviour of TPS. Therefore, the effect of 1-ethyl-3-methylimidazolium acetate (Emim Ac) and 1-ethyl-3-methylimidazolium chloride (Emim Cl) as plasticizers on the thermal behaviour of TPSs was investigated in this paper. The TPSs were prepared with two different ILs/water ratios; 1:4 and 2:3. The addition of Emim Ac as plasticizer shows lower onset temperature of the thermal degradation than Emim Cl. The presence of Emim Ac promotes the thermal degradation of starch molecules, leaving an amount of around 13% of residue. The results indicated that TPS plasticized by Emim Ac improved the thermal behaviour of TPSs than Emim Cl. Therefore, this can conclude that Emim Ac is more suitable than Emim Cl as a plasticizer for TPS. © 2017 The Authors.